2020
DOI: 10.1080/10253866.2020.1802258
|View full text |Cite
|
Sign up to set email alerts
|

Fashionable detachments: wardrobes, bodies and the desire to let go

Abstract: Consumers are increasingly asked to "empty out their closets," to "declutter" or in other ways detach themselves from the textile surplus of their wardrobes. In this article, fashion is examined as a process of detachment. Building on ethnographic wardrobe interviews, wardrobe clearances and group discussions with consumers, detachment is viewed as a fundamental, yet underexamined, process of fashion practices. Drawing on the queer phenomenology of Sarah Ahmed, we observe how the informants express a desire to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…cused on analyzing consumer perspectives on fashion sustainability [33][34][35][36][37][38][39][40][41], since it is extremely important to identify the main causes that drive consumption habits towards or away from sustainable fashion practices.…”
Section: Methodsmentioning
confidence: 99%
“…cused on analyzing consumer perspectives on fashion sustainability [33][34][35][36][37][38][39][40][41], since it is extremely important to identify the main causes that drive consumption habits towards or away from sustainable fashion practices.…”
Section: Methodsmentioning
confidence: 99%
“…Niinimäki and Armstrong (2013) found that once garments had been owned for 22–24 years, the frequency of wear among loved garments begins to decline, and storage can be used to preserve precious memories. Allowing a space to be dedicated to nostalgic storage allows users to keep valued garments without the chaos of an overcrowded wardrobe (Mellander & Petersson McIntyre, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Outerwear (e.g., coats, outdoor jacket) is a garment that is often seasonally stored during warmer months, though many other garment types could be included (Niinimäki & Armstrong, 2013). Nostalgic storage is defined as the careful storage of items that preserve memories (Mellander & Petersson McIntyre, 2021). Niinimäki and Armstrong (2013) found that once garments had been owned for 22-24 years, the frequency of wear among loved garments begins to decline, and storage can be used to preserve precious memories.…”
Section: Wardrobe Engagementmentioning
confidence: 99%
“…While students like the idea of fashion companies accepting returned fashion items that customers no longer use, they are not willing to return their items to fashion stores for recycling to the same degree. This may be because discarding these items may in some way be related to letting go of their dreams and aspirations for the future ( Mellander and Petersson McIntyre, 2020 ). Companies cannot make their supply chains truly sustainable unless consumers accept responsibility for returning their unwanted clothing ( Ki et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%